SCREENING OF ANTIBACTERIAL ACTIVITY OF FIVE DIFFERENT SPICES (AJWAIN, CORIANDER, CUMIN, FENNEL, AND FENUGREEK) AGAINST PATHOGENIC BACTERIAL STRAINS - S, Salma; Ramakrishnan, Lalitha; J, Vinothini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study was focussed on an evaluation of antibacterial activities of aqueous and alcoholic extracts of commonly consumed spices, namely, Ajwain (Trachyspermum ammi), Coriander (Coriandrum sativum), cumin (Cuminum cyminum), fennel (Foeniculum vulgare), and Fenugreek (Trigonella foenum-graecum). Methods: This study includes the antibacterial effects of spices against six bacterial strains, namely, Escherichia coli, Klebsiella pneumonia, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhi, and Staphylococcus aureus to compare their antibacterial effects by the paper disc agar diffusion method with three antibiotics such as amikacin, chloramphenicol, and vancomycin. Results: According to findings, it is determined that inhibitory activity was detected on aqueous and alcoholic extracts of Ajwain, aqueous extract of cumin and on alcoholic mixed spice sample.